Implementing a project office at Curtin University - lessons learnt. - Baccarini, David (Project Management Global, 2002)
This paper describes the lessons learnt is implementing a project office at Curtin University. The author was a member of the project team for Phases 1, 2 and 3.The use of the Project Office (PO) has a long history dating back to the 1930s (Kwak & Dai, 2000). The interest in project offices has grown significantly over recent times because of the explosion of projects that organisations have to undertake to survive and proper (Dinsmore, 2000). Research shows 85% of POs in the private sector have existed for less than three years whilst 75% in the public sector have been in existence for more than three years (Block & Frame, 2001). Clearly, Curtin University is not alone in its efforts to implement a PO.